Male body image and related behaviors surrounding the ideal mesomorphic physique: A multi-phase mixed method investigation - Bottamini, Gina (University of Ottawa (Canada), 2006)
The purpose of the research presented herein was to gain a better understanding of male body image-related behaviors through a multi-phase mixed method approach. With research revealing a noted increase in muscularity in media representations of the male physique in the latter part of the twentieth century, context to the present day ideal male physique was first provided via the examination of sculptures and paintings from ancient Greece to the latter part of the 19th century (phase I). The ideal male physique was further examined in the qualitative phase of the research (phase II) where semi-structured interviews with 11 males were conducted. Data obtained from the interviews also aided in the construction of the Male Body Image Behavior Questionnaire (MBIBQ). The structure and length of the MBIBQ as well as its psychometric properties were next examined with a total of 550 participants in phases III and IV respectively. The examination of art representations of the male physique revealed varied depictions of a muscular ideal with interceding portrayals of thin or nonrealistic interpretations. A number of themes emerged from the qualitative data including the ideal physique and attributes, influences, psychosocial consequences, motivations, and behaviors. An interesting finding was that a few of the males expressed a preference for a female interviewer suggesting that cross-gender interviewing should be considered when examining body image in males. The results from the exploratory principal components and confirmatory factor analyses conducted in phase III revealed that the MBIBQ is comprised of four subscales; weight gain, weight loss, avoidance, and appearance. The more extreme behaviors on the preliminary version of the MBIBQ did not meet the criteria for item inclusion and were thus deleted, suggesting that although males may indicate knowledge of more extreme behaviors, their actual utilization may be limited. Phase IV of the research, conducted with 253 participants, showed preliminary evidence of convergent, discriminant, and concurrent validity as well as test-retest validity for the MBIBQ. The MBIBQ is the first of its kind to address several dimensions of body image behaviors in males. The educational implications of the findings for school-based programs are discussed.
Keywords: Education, Educational Psychology.; Education, Health.